Factors associated with initial AstraZeneca vaccine knowledge, attitudes, and uptake among hospital nurses: A cross-sectional study in Ghana's Upper East region. - Atongu, Simon Ferguson (Public Library of Science (PLoS), 2024)
10.1371/journal.pgph.0002674